Behavior of Self-Compacting Concrete-Filled Steel Tube Columns with Inclined Stiffener Ribs under Axial Compression - Liang, W.; Dong, J.F.; Yuan, S.C.; Wang, Q.Y. (Проблемы прочности, 2017)
This study outlines the experimental investigation of the steel tube columns filled with selfcompacting concrete under axial compression. The effect of the stiffening arrangements and the concrete strength on the properties of the concrete-filled steel tube columns having stiffeners of different geometric dimensions has been investigated. The failure modes, ultimate loads, stiffness, ductility and strain response of the concrete-filled steel tube columns during the experiment have been analyzed. The results imply that the local buckling of the steel tubes can be delayed by the stiffeners. Moreover, the specimen with the four-sided stiffening arrangement possesses higher stiffness and better ductility as compared with the two-sided one. The test results also demonstrate that the proposed stiffening schemes can improve the ultimate compressive capacity. The predicted ultimate loads have been compared using the existing codes, and the modified formula has been proposed. A good agreement between the theoretical and the experimental results is observed.